Terrestrial radiative cooling: Using the cold universe as a renewable and sustainable energy source - Yin, Xiaobo; Yang, Ronggui; Tan, Gang; Fan, Shanhui (Science (American Association for the Advancement of Science), 2020)
Photonic materials designed at wavelength scales have enabled a range of emerging energy technologies, from solid-state lighting to efficient photovoltaics that have transformed global energy landscapes. Daytime passive radiative cooling materials shed heat from the ground to the cold universe by taking advantage of the terrestrial thermal radiation that is as large as the renewable solar energy. Newly developed photonic materials permit subambient cooling under direct sunshine, and their applications are expanding rapidly enabled by scalable manufacturing. We review here the recent advancement of daytime subambient radiative cooling materials, which allow energy-efficient cooling and are paving the way toward technologies that harvest the coldness from the universe as a new renewable energy source.